2021
DOI: 10.3390/pathogens10081010
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Biology of the Emerging Tembusu Virus

Abstract: Reported for the first time in 1955 in Malaysia, Tembusu virus (TMUV) remained, for a long time, in the shadow of flaviviruses with human health importance such as dengue virus or Japanese encephalitis virus. However, since 2010 and the first large epidemic in duck farms in China, the threat of its emergence on a large scale in Asia or even its spillover into the human population is becoming more and more significant. This review aims to report current knowledge on TMUV from viral particle organization to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 140 publications
(169 reference statements)
0
29
0
Order By: Relevance
“…Currently, DTMUV is widely distributed and becomes endemic in duck populations in several Asian countries, causing significant DTMUV in the infected ducks (Ninvilai, Limcharoen, et al, 2020), detection of DTMUV-specific antibodies is often used for diagnosis of DTMUV infection. Although SN test is considered the gold standard for DTMUV-specific antibody detection (Hamel et al, 2021) Notably, our results demonstrated that HI test exhibited a higher specificity, overall agreement, and stronger positive correlation with SN test for the detection of antibodies against DTMUV than those by IFA test. This finding would be explained partly by the fact that SN and HI tests both primarily measure neutralizing antibodies targeted the viral envelope glycoprotein, whereas IFA test detects antibodies against a variety of structural and nonstructural proteins of the virus (Niedrig et al, 2008;Takahashi et al, 1986).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Currently, DTMUV is widely distributed and becomes endemic in duck populations in several Asian countries, causing significant DTMUV in the infected ducks (Ninvilai, Limcharoen, et al, 2020), detection of DTMUV-specific antibodies is often used for diagnosis of DTMUV infection. Although SN test is considered the gold standard for DTMUV-specific antibody detection (Hamel et al, 2021) Notably, our results demonstrated that HI test exhibited a higher specificity, overall agreement, and stronger positive correlation with SN test for the detection of antibodies against DTMUV than those by IFA test. This finding would be explained partly by the fact that SN and HI tests both primarily measure neutralizing antibodies targeted the viral envelope glycoprotein, whereas IFA test detects antibodies against a variety of structural and nonstructural proteins of the virus (Niedrig et al, 2008;Takahashi et al, 1986).…”
Section: Discussionmentioning
confidence: 63%
“…Due to transient viremia and short‐term detection of DTMUV in the infected ducks (Ninvilai, Limcharoen, et al., 2020), detection of DTMUV‐specific antibodies is often used for diagnosis of DTMUV infection. Although SN test is considered the gold standard for DTMUV‐specific antibody detection (Hamel et al., 2021), this test is expensive, laborious, and time‐consuming. Apart from SN test, HI and IFA tests are the standard serological tests commonly used for identifying antibodies to several flaviviruses and generally show good correlations with SN test (De Paula & Fonseca, 2004; Niedrig et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, although the four countries are in Southeast Asia and South America, they are all located within the region 30° south to 30° north latitude. All four countries have tropical or subtropical rainforest climates, with high temperatures and high humidity throughout the year, and this environment is conducive to the spread and mutation of the virus ( Hamel et al, 2021 ; Hattakam et al, 2021 ; Munoz et al, 2021 ; Ngim et al, 2021 ; Sriburin et al, 2021 ). In subtropical rainforests, PCV3 is not the only prevalent virus; other viruses such as the Zika virus and dengue virus are also prevalent, among others ( Hamel et al, 2021 ; Hattakam et al, 2021 ; Munoz et al, 2021 ; Ngim et al, 2021 ; Sriburin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%